A redefinition of the genus Hemichaeta Steyskal, new status (Diptera; Micropezidae; Taeniapterinae) - Marshall, Stephen A.; Jackson, Morgan D. (Zootaxa, 2014)
We here reconsider the status of subgenus Hemichaeta Steyskal, concluding that there is no justification to keep it in the genus Poecilotylus Hennig. Hemichaeta is thus removed from Poecilotylus and elevated to generic status with Hemichaeta scutellata (Cresson) as the type and only included species. Hemichaeta scutellata is fully redescribed, including the previously undescribed male and female terminalia.